Koncepcja kołowego modelu oceny finansowej kondycji przedsiębiorstwa - Kowalak, Robert (Conception of wheel of corporate financial analysis, 2008)
The article presents the conception of wheeled model of the assessment of the financial position of a company. This model is based on universally financial ratios in classical financial analysis. In the paper, the author uses ratios taken by auditors at studying financial statement of companies
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1199, s. 53-59